BETTERMENT OF DICLOFENAC-INDUCED NEPHROTOXICITY BY PENTOXIFYLLINE THROUGH MODULATION OF INFLAMMATORY BIOMARKERS - AL-KURAISHY, HAYDER M.; AL-GAREEB, ALI I.; HUSSIEN, NAWAR RAAD (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Diclofenac-induced nephrotoxicity is caused by oxidative stress which leads to lipid peroxidation and formation of free radicals. Pentoxifylline can ameliorates renal tissue injury by its anti-inflammatory, antifibrotic, and antioxidant effects, so it mitigates the progression of renal diseases. Therefore, the aim of this study was to evaluate the nephroprotective effects of pentoxifylline on diclofenac-induced nephrotoxicity in rats. Methods: A total of 30 male Sprague-Dawley rats were allocated into three groups, Group 1 (n=10): Rats treated with distilled water 5 ml/kg plus normal saline 5 ml/kg for 12 days, Group 2 (n=10): Rats treated with distilled water 5 ml/kg plus diclofenac 15 mg/kg for 12 days, and Group 3 (n=10): Rats treated with pentoxifylline 100 mg/kg plus diclofenac 15 mg/kg for 12 days. Blood urea, creatinine, malondialdehyde (MDA), superoxide dismutase (SOD-1), glutathione reductase (GSH), neutrophil gelatinase associated lipocalin (NGAL), kidney injury molecules (KIM-1) vitronectin (VTN), integrin (ITG) , interleukin-18 (IL-18) and cystatin-C were used to measure the severity of nephrotoxicity. Results: Diclofenac-induced nephrotoxicity led to significant elevation in blood urea, serum creatinine, MDA, IL-18, KIM-1, NGAL, serum ITG, and VTN with decrease of SOD-1 and GSH sera levels p<0.05. Treatment with pentoxifylline showed no significant effect on all biomarker levels compared to diclofenac group except on serum level KIM-1 and serum VTN, p<0.05. Conclusion: Pentoxifylline produced significant nephroprotective effect on diclofenac-induced nephrotoxicity through modulation of inflammatory biomarkers.